(untitled) (Costos y Gestión, 2020)
The advance of the changes caused by the behavior of the actors in the so-called “New Economy” has impacted on decisions and marketing models. These changes have been picked up by authors in a fundamental area of business administration, such as “Marketing”. Now, the key to the change in the development of the so-called “relational marketing” has been to accept that all business management models, on which business has advanced, have been based on products. While, from the shortening of life cycles and their ephemeral existence in the markets, the commercial perspective is reorienting itself to build and consolidate the relationship with the client or the segment to which it belongs. Based on the topics of this new perspective, developed by Pablo Fernández in his book The 6 Rs of Marketing: Six proven strategies to monetize his client portfolio, it is possible to structure a cost information platform to facilitate the commercial management of business with this new approach. The main objective of this paper is to propose the new costing units that will have to be defined, to assign the costs of the actions in each of them and to allow the business manager to make decisions about these key factors of the model, considering it as a second complementary level of product-based marketing.